The role of religiosity in the opposition to drug use - Stylianou, Stelios (My University, 2004)
This study examines the causal mechanism linking religiosity to opposition to drug use. Using an electronic mail survey of university students, data were obtained about the participants' religious beliefs, their perceptions of drug use, and their attitudes toward the use of six common drugs (alcohol, cigarettes, cocaine, heroin, LSD, and marijuana). Based on the data, path models were estimated for each substance to investigate the causal structure underlying four constructs: religiosity, perceived immorality of drug use, perceived self-harm of drug use, and attitudes toward the control of drug use (control attitudes). The results support that religiosity affects control attitudes indirectly through perceived immorality of drug use.
Keywords: Crime seriousness; Drug use; Morality; ReligiosityS; Social control